Volcanism, sedimentation and massive sulfide mineralization in a Late Cretaceous arc-related basin, Eastern Taurides, Turkey - Bölücek, C; Akgül, M; Türkmen, I (Pergamon-Elsevier Science Ltd, 2004)
Late Cretaceous arc volcanism and associated massive sulfide mineralizations occur in the Eastern Taurus Mountains. The mineralizaions are related to felsic (dacitic-rhyolitic) volcanic rocks which, together with basement rocks, form the lowermost levels of a 5000m thick volcano-sedimentary sequence, and are restricted to a few levels within the sequence. Basaltic rocks, which are intruded by tonalite and dacite, form the base of the volcano-sedimentary sequence. The dacitic-rhyolitic rocks are overlain by a volcano-sedimentary with andesitic-dacitic flows. The flows do not contain any mineralization. This succession starts with volcanic breccia and tuffs at the base. passing into crystal-rich sandstone, and pelagic mudstone with tuffite intercalations, and ends with marls intercalated with sandstone balsalt and peridotite olistoliths. The felsic rocks bear stockwork and disseminated types of mineralization. The massive sulfide mineralization has a simple mineral assemblage of pyrite, chalcopyrite, bornite and sphalerite. Optical microscopic examination of pyrites from Derince Massive Sulfide Deposits reveals that the pyrites are commonly seen in framboidal and cubic forms. The geochemistry of the magmatic rocks and sedimentary facies associations indicate that the mineralizations in the Derince were developed in an intra-arc environment. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: massive sulfide; Late Cretaceous; Eastern Tauride; Turkey